COLLABORATION PROCESS IN COMMUNITY EMPOWERMENT BASED ON TOURISM VILLAGE IN PANTAI KARANG JAHE, PUNJULHARJO REMBANG VILLAGE - Nur Jihan Septiani; Herbasuki Nurcahyanto; Aufarul Marom (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2021)
AbstractCollaboration of Stakeholders at Karang Jahe Beach, Punjulharjo Village is an effort made to build the community's economy through the utilization of the village's original potential. This research aims at the process of forming stakeholder collaboration in empowerment in the Tourism Village of Punjulharjo Rembang. The research method used is descriptive qualitative. Sources of data in this study were obtained from interviews, observations, and documentation. The technique of selecting informants was carried out using purposive sampling. The collaborative process of stakeholders is seen from the sub-phenomenon of mutual understanding, commitment, communication and temporary impacts that have been carried out optimally. A sub-phenomenon that is less than optimal is communication in the empowerment capacitating stage. Communication between BUMDes Punjulharjo, Karang Jahe Beach Management Unit, Tourism Awareness Group, and Culture and Tourism Office is still not optimal. Communication is only effective in the internal environment, namely between BUMDes and the Management Unit. The driving factor for stakeholder collaboration in Karang Jahe Beach, Punjulharjo Village is the quality of stakeholder resources, tourism finance, and full support from the District Government. The inhibiting factor for stakeholder collaboration is the difference in interests between stakeholders and the passive community in empowerment. Suggestions that can be given are building information transparency among stakeholders, building community participation in empowerment, changing the way people perceive investors and sustainable empowerment of supporting stakeholders.